Dystonia and ataxia progression in spinocerebellar ataxias. (December 2017) - Kuo, Pei-Hsin; Gan, Shi-Rui; Wang, Jie; Lo, Raymond Y.; Figueroa, Karla P.; Tomishon, Darya; Pulst, Stefan M.; Perlman, Susan; Wilmot, George; Gomez, Christopher M.; Schmahmann, Jeremy D.; Paulson, Henry; et al.
Abstract: Background: Dystonia is a common feature in spinocerebellar ataxias (SCAs). Whether the presence of dystonia is associated with different rate of ataxia progression is not known. Objectives: To study clinical characteristics and ataxia progression in SCAs with and without dystonia. Methods: We studied 334 participants with SCA 1, 2, 3 and 6 from the Clinical Research Consortium for Spinocerebellar Ataxias (CRC-SCA) and compared the clinical characteristics of SCAs with and without dystonia. We repeatedly measured ataxia progression by the Scale for Assessment and Rating of Ataxia every 6 months for 2 years. Regression models were employed to study the association between dystonia and ataxia progression after adjusting for age, sex and pathological CAG repeats. We used logistic regression to analyze the impact of different repeat expansion genes on dystonia in SCAs. Results: Dystonia was most commonly observed in SCA3, followed by SCA2, SCA1, and SCA6. Dystonia was associated with longer CAG repeats in SCA3. The CAG repeat number in TBP normal alleles appeared to modify the presence of dystonia in SCA1. The presence of dystonia was associated with higher SARA scores in SCA1, 2, and 3. Although relatively rare in SCA6, the presence of dystonia was associated with slower progression of ataxia. Conclusions: The presence of dystonia is associated with greater severity of ataxia in SCA1, 2, and 3, but predictive of a slower progression in SCA6. Complex genetic interactions among repeat expansion genes can lead to diverse clinical symptoms and progression in SCAs. Highlights: Dystonia is a common feature in SCA3, particularly those with longer CAG repeats. Dystonia in SCA1 is associated with a shorter CAG repeat length of TBP. Dystonia is associated with more severe ataxia in SCA1, 2, and 3. Dystonia is associated with a slower rate of ataxia progression in SCA6.